Implementasi Manajemen Mutu Terpadu dalam Mengembangkan Budaya Religius di SMAS Ulumul Islam Tanah Jambo Aye Kabupaten Aceh Utara - Faradila, Faradila (Medan Resource Center, 2024)
The aim of this research is to find out how to implement integrated quality management in developing religious culture at SMAS Ulumul Islam and the problems it faces. This research was conducted as a qualitative type of research and used a field research approach. The results of the research show that the implementation of integrated quality management in the development of religious culture at SMAS Ulumul Islam produces several results, such as: a) continuous improvement through regular meetings, support from foundations, and support from Islamic boarding schools, b) implementation of standards with full implementation of religious culture in schools and in everyday life, c) cultural change through the application of religious culture in every activity, religious culture schedule, and SMAS Ulumul Islam faces several challenges when implementing integrated quality management to develop religious culture. These include undisciplined students, lack of parental funds, inconsistent interest in learning, and changing boarding school rules.